2022
DOI: 10.21203/rs.3.rs-1099620/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upregulation of P2Y12 inhibits chondrocyte apoptosis in lumbar osteoarthritis through PI3K/AKT signaling pathway

Abstract: BackgroundLumbar facet osteoarthritis (FJOA) is one of the major causes of severe low back pain and disability worldwide. However, the underlying mechanism of cartilage degeneration in FJOA remains unclear. MethodsThe rats were randomly divided into non-operation group (n=20) and operation group (n=10). In the operation group, MIA (Sigma, 200mg/mL) was injected into the right L4/5 facet process by blunt nanoneedle 26 (WPI, Sarasota, FL, USA) under the control of injection pump. The final injection volume was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In recent years, there has been increasing evidence that regulation of the cell cycle through the PI3K/Akt signaling pathway can inhibit IL-1β-induced apoptosis and inflammatory. 85,86 First, Cai et al found that compared to normal cells and tissues, apoptosis was increased in IL-1β-treated articular chondrocytes accompanied by downregulation of PI3K mRNA levels, 4 which demonstrated that PI3K is associated with apoptosis. Next, Guo et al found that 17β-estradiol attenuated IL-1β-induced early apoptosis in nucleus pulposus cells by increasing the expression of activated mechanistic target of rapamycin (mTOR) and decreasing the expression of activated caspase-3, in intervertebral disc lesions.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been increasing evidence that regulation of the cell cycle through the PI3K/Akt signaling pathway can inhibit IL-1β-induced apoptosis and inflammatory. 85,86 First, Cai et al found that compared to normal cells and tissues, apoptosis was increased in IL-1β-treated articular chondrocytes accompanied by downregulation of PI3K mRNA levels, 4 which demonstrated that PI3K is associated with apoptosis. Next, Guo et al found that 17β-estradiol attenuated IL-1β-induced early apoptosis in nucleus pulposus cells by increasing the expression of activated mechanistic target of rapamycin (mTOR) and decreasing the expression of activated caspase-3, in intervertebral disc lesions.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…In recent years, there has been increasing evidence that regulation of the cell cycle through the PI3K/Akt signaling pathway can inhibit IL‐1β‐induced apoptosis and inflammatory 85,86 . First, Cai et al found that compared to normal cells and tissues, apoptosis was increased in IL‐1β‐treated articular chondrocytes accompanied by downregulation of PI3K mRNA levels, 4 which demonstrated that PI3K is associated with apoptosis.…”
Section: Introductionmentioning
confidence: 99%